Internalisasi Nilai Nilai Pendidikan Pesantren (Analisis Diskriptif Penerapan Panca Jiwa di Pondok Pesantren Al Fattah Pecalongan Sukosari Bondowoso) - Rusydi, Rusydi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Pesantren as an educational institution based on religious values â€‹â€‹that are instilled as an effort to build the character of students through habituation (tatsqief). It aims to print Muslims into insan kamil (perfect humans) and have and master the religious sciences that are lived and practiced sincerely. The Islamic boarding school functions itself as an institution that produces outputs and outcomes as the ideals of the ulama of an Islamic boarding school through educational and teaching activities. Education and teaching are so complex, this is equivalent to the theory which says that "Thus the three aspects of education are cognitive, affective and psychomotor. All of them are given simultaneously and in balance to students. The santri besides living in social situations and shortages for 24 hours day and night continuously are always in an educational atmosphere under the direct guidance of kyai and ust ". This discussion focuses on finding answers about how the five souls as pesantren values â€‹â€‹are applied at Al Fattah Islamic boarding school, what are the implications for the integrity of the character of the santri. The author presents it in the form of a descriptive analysis which is then reduced by using the theory of Mile and Hiberman so that it becomes a real data unit, between interviews, observations and documentation studies are presented in their entirety. The application of the five souls of the pesantren at the Al-Fattah Islamic boarding school is carried out with more emphasis on the delivery and guidance directly (Ù…ÙØ¨ÙŽØ§Ø´ÙÙŠÙ’Ø±Ù) or indirectly (ØºÙ‹ÙŠÙ’Ø±ÙÙ…ÙØ¨ÙŽØ§Ø´ÙÙŠÙ’Ø±Ù) in various ways. Namely by habituation, and other forms of activity programs, both core activities and extra activities. The impact of the application of the five souls of the pesantren into a character that is reflected in the dynamics of education is sincere in learning, working and serving, independence, ukhuwah Islamiyah, simplicity, free but Islamic.